Air Connectivity and Foreign Direct Investments The economic effects of the introduction of new routes - Renato Redondi; Mariasole Bannò; Marco Mutinelli (European Regional Science Association (ERSA), 2011)
By integrating the theoretical perspective of international business, economic geography and transportation science, we develop a novel framework to investigate the relationship between the localization of foreign direct investments (FDI) and air connectivity. In particular the key research question for this study is whether and in which ways the spatial network structure offered by the global airline system contributes to the development of both outward and inward FDI. Due to the widespread diffusion of multinationals, air travel is often required as a mean to engage face-to-face contacts at various levels within the organization, by the board of directors, managers, entrepreneurs and staff. The introduction of a new route, by reducing transport costs, should increase the likelihood of FDI exchange between the regions newly connected. Several studies have already analyzed the linkage between air traffic and various urban or regional characteristics, among which its degree of internationalization, and have unanimously demonstrated that the geography of FDI is related to the desire of large multinational companies to easily access the main international airports. However, literature traditionally focused on larger multinational companies located in global cities. To the best of our knowledge, no study has yet considered the effect of air travel on FDI by SMEs in secondary regions. We aim to test whether the geography of FDI between Italy and Europe is related to the desire of overseas companies to directly access international airports. This paper employs an event study methodology to determine the impact of new routes on the generation of both inward and outward FDI considering both SMEs and large companies. In particular, we built an original database covering the period 1997-2010 where for each FDI between Italy and Europe we collected information about the locations of both the overseas company and the newly created subsidiaries at a municipality level. That enables us to estimate the impact of a new route to the FDI subsequently generated between the catchment areas of the connected airports. We account for the existence of a possible endogeneity bias by considering several control variables.
Keywords: 330